Simulation of identifying shortest path walkway in library by using ant colony optimization - Chui Teng, Chan (2012)
A research is proposed based on Ant Colony Optimization for solving the shortest path problem in library.This is a research that the algorithm is aim to implement on a robot. The robot is used to walk around in the library to collect books from all the tables and put on book shelves.However, command prompt window will use to shows the result which is the shortest path.People nowadays are more concern about the efficiency of work,this may happen in library as well. Therefore,by determining the shortest path will help in reducing the time consume problem.This project is developed by starting with designing the workflow diagram as well as the design of the output interface.The work flow is the guide for the process of development.In between,Heuristic Approach is used to determine the entire possible paths at first,then Ant Colony Optimization algorithm will be implemented to search for the final and the shortest path. The system is used to be error free and the algorithm can effectively solve the shortest path problem.